Therapists and Academic Writing: “Once upon a time psychotherapy practitioners and researchers were the same people” - McBeath, Alistair; Bager-Charleson, Sofie; Abarbanel, Avigail (European Journal for Qualitative Research in Psychotherapy, 2019)
The views and feelings of psychotherapists around academic writing were explored using a mixed methods approach. An on-line survey completed by 222 psychotherapists produced both quantitative and qualitative data with the latter being subject to a Reflexive Thematic Analysis. Significant numbers of participants lacked confidence about participating in academic writing. Fear of rejection, not being good enough and not knowing what is required were prominent underlying factors. Current academic writing was viewed as overly intellectual, not focused on clinical practice and the preserve of academics and not practicing therapists. Difficulty in accessing academic material lying behind pay walls was another factor limiting participation in academic writing as well as a lack of formal support. Clinical relevance and clarity of expression were viewed as the key factors of good academic writing. There was overwhelming support for academic writing to be a core skill taught in formal psychotherapy trainings.